Research on Anode Catalysts for Methanol Fuel Cells - Wang Qiuye (MATEC Web of Conferences)
Developing effective and sustainable energy conversion technologies is crucial given the rising demand for energy worldwide and the focus on environmental preservation. As a clean energy technology, methanol fuel cells have a broad application prospect. However, the performance of anodic hydrogen oxidation catalysts still faces many challenges, such as high cost, low catalytic efficiency and easy poisoning. This paper, the research status of anodic hydrogen oxidation catalysts for methanol fuel cells is reviewed in detail. Among them, Pt-based catalysts include single-component, binary, ternary and multicomponent catalysts. They add other metals as co-catalysts to improve the problems of carbon dioxide poisoning, metal corrosion in acidic environments, and cost. The non-Pt-based catalyst also has a good catalytic effect to some extent, and it is expected to make the commercial production of methanol fuel cells a reality because of its cost reduction. Besides, future development trends were also prospected, with the aim of providing theoretical guidance for improving the efficiency of methanol fuel cells and promoting their commercial application.